Cardiovascular medical device failure: Using five-week moving averages to assess adverse event report data - Elsa S. Zhou; Sujata K. Bhatia (Review of Economic Analysis (REA), 2022)
The COVID-19 pandemic had a variety of effects on the healthcare system, including the interruption of regular cardiology practices. We examined the pandemic's effects on cardiovascular medical device failure by investigating trends in the number of reports of adverse events of several cardiovascular medical devices over the span of three years, including the first year of the pandemic. Specifically, we used data from the FDA's MAUDE database, calculating the five-week moving average of adverse events associated with both implantable cardioverter defibrillators and coronary drug-eluting stents. We previously reported a 46% decrease in reported deaths attributed to ICDs and a 27% decrease in reported injuries attributed to coronary DES. We use a five-week moving average and confirm a 46% decrease in reported deaths attributed to ICDs, report a 9.8% increase in ICD-attributed malfunctions, and confirm a 27% decrease in reported injuries attributed to coronary DES. The different effects of the pandemic on these adverse event report trends, even within one device, show there are more factors to consider than explanations such as underreporting which would be expected to affect most medical devices relatively homogeneously.
Keywords: I19; 330; cardiology; medical device; adverse event; Covid-19